Retroperitoneal lymphangiectasia: a great clinical masquerade - Manwar, Siddhant Uttam; Joshi, Manisha Vishnu; Shetty, Devdas Sudhakar; Bhalerao, Upendra Diwakar (International Journal of Research in Medical Sciences, 2020)
Retroperitoneal lymphangiectasia is a very rare lymphatic disorder characterized by abnormal proliferation of lymphatics. We present series of 3 cases of retroperitoneal lymphangiectasia which are diagnosed in our institute with the help of Ultrasonography (USG), Computed Tomography (CT) and Magnetic resonance imaging (MRI) of abdomen and pelvis with unusual clinical presentation. We include clinical features and imaging findings of this disorder with its pathogenesis and diagnosis. Two of the cases were clinically masquerading as hernia and one case was mimicking varicocele. Thorough clinical examination and USG, colour Doppler, CT and MRI are extremely helpful imaging investigation that aid in differentiating these lesions from hernia/ varicocele and the cross sectional imaging like CT and MRI can depict the anatomical extent of the disease.